PSYCHOLOGY AND HEALTH OF INDONESIAN UMRAH PILGRIMS: EXPLORING MENTAL AND PHYSICAL WELL-BEING DURING THE JOURNEY - Abdallah Al-Shreifeen, Iyad; Marlinda, Marlinda (Lafadz Jaya Publisher, 2025)
This study examines the psychological and health aspects of Indonesian pilgrims performing Umrah, a spiritual journey to Mecca. Given the importance of Umrah as a religious obligation for many Muslims, understanding the psychological and physical challenges faced by the pilgrims is critical. The research explores factors such as stress, anxiety, physical exhaustion, and social interactions during the pilgrimage, focusing on the specific experiences of Indonesian pilgrims. A mixed-methods approach was used, including surveys and interviews, to gather data from 200 participants. The findings highlight that while the spiritual experience of Umrah can bring a sense of peace and fulfillment, the physical and psychological challenges of the journey—such as fatigue, homesickness, and health concerns—are significant. Pilgrims’ health and psychological well-being are closely intertwined, with spiritual experiences acting as both a source of strength and stress. These insights are crucial for religious organizations, travel agencies, and healthcare providers to better prepare pilgrims for the physical and mental demands of Umrah, ensuring a more enriching and healthier pilgrimage experience. The study also suggests recommendations for improving the support systems for Indonesian pilgrims and the importance of mental health care in religious travel.